2022
DOI: 10.5829/ije.2022.35.05b.07
|View full text |Cite
|
Sign up to set email alerts
|

Partial Replacement of Conventional Material with Stabilized Soil in Flexible Pavement Design

Abstract: Due to rapid urbanization and industrialization, the construction of roads increases rapidly for easy and fast transportation. Adequate land is not available everywhere to construct good roads; hence, roads are forcefully built on locally available soil such as loose soil or expansive soil. In this paper, an experimental investigation was carried out on low plastic soil (LPS) to enhance engineering properties by using chemical soil stabilization (fly ash-based geopolymer). The design of flexible pavement thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A modified proctor test was conducted and OMC & MDD values of fly ash and fly ash-binder mixes were found. OMC & MDD values of F1, F2 and F3 fly ashes were 18.9%, 1.34 g/ cm 3 ; 19%, 1.35 g/ cm 3 and 25.6%, 1.38 g/cm 3 . OMC in the range of 18.5% to 19.0%, 18.0%-19.0% and 25.4%-25.5%, while MDD in the range of 1.38 g/ cm 3 -1.41 g/ cm 3 , 1.40 g/ cm 3 -1.42 g/ cm 3 and 1.37 g/ cm 3 -1.38 g/ cm 3 were found for F1, F2 and F3 fly ash-binder mixes, respectively.…”
Section: Compaction Test Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…A modified proctor test was conducted and OMC & MDD values of fly ash and fly ash-binder mixes were found. OMC & MDD values of F1, F2 and F3 fly ashes were 18.9%, 1.34 g/ cm 3 ; 19%, 1.35 g/ cm 3 and 25.6%, 1.38 g/cm 3 . OMC in the range of 18.5% to 19.0%, 18.0%-19.0% and 25.4%-25.5%, while MDD in the range of 1.38 g/ cm 3 -1.41 g/ cm 3 , 1.40 g/ cm 3 -1.42 g/ cm 3 and 1.37 g/ cm 3 -1.38 g/ cm 3 were found for F1, F2 and F3 fly ash-binder mixes, respectively.…”
Section: Compaction Test Resultsmentioning
confidence: 92%
“…More aggregate is required for the fast infrastructure development of a country. Mining of natural aggregate leads to severe environmental impacts and consumption of natural resources [3].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows variation of UCS value for various fly ash quarry dust mixes obtained after curing for 3, 7 and 28 days. The strength gain within the mixes containing fly ash is attributed to the presence of silica and alumina [30]. It was observed that as the percentage of quarry dust Variation of unconfined compressive strength with varying quarry dust addition to fly ash addition to fly ash increased, the strength of the mix decreased.…”
Section: Unconfined Compressive Strength (Ucs) Testmentioning
confidence: 99%
“…Previous researchers investigate on any possible techniques or practices to enhance strength properties of peat soils. Various soil improvement techniques such as utilize *Corresponding Author Institutional Email: bayat.m@pci.iaun.ac.ir (M. Bayat) mechanical energy and/or man-made materials have been used to improve the mechanical characteristics of weak or soft soils in practice for many years [4][5][6]. The problems of structures situated on weak or soft deposits are represented by significant settlement, low shear and compressive strength parameters [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%